Higher Education Leadership and Policy Implementation: A Qualitative Exploration of Strategic Decision-Making - Dewiana Novitasari; Didi Sutardi; Firdaus Putra; Masduki Asbari; Nelson Silitonga (International Journal of Management and Economic Research (IJOMER), 2025)
This qualitative study explores the strategic decision-making practices of higher education leaders in Indonesia during the implementation of national policy directives. Drawing on in-depth, semi-structured interviews and document analysis, the research employs a thematic analysis approach to investigate how rectors, deans, and senior academic administrators interpret, negotiate, and enact educational reforms. The findings reveal three interrelated leadership dynamics: strategic mediation, symbolic and practical alignment, and distributed decision spaces. Through a dialectical engagement with strategic leadership and institutional theory, the study develops an integrative conceptual model that reconceptualizes policy implementation as an iterative and context-sensitive process. This model contributes theoretical novelty by synthesizing competing paradigms and offers practical insights for advancing reflexive, policy-literate leadership in complex governance environments.